HUBUNGAN ANTARA PEMAHAMAN PESERTA DIDIK TERHADAP TATA TERTIB DENGAN KEDISIPLINANNYA DI SMPN 1 LEMBEYAN MAGETAN - Rosanti, Astia Herlitania; Agus Satmoko Adi (Universitas Negeri Surabaya (Unesa), 2024)
This research aims to test whether or not there is a relationship between class VIII students' understanding of their discipline at SMPN 1 Lembeyan Magetan. This research uses quantitative research with a sample size of 60 respondents, namely class VIII students at SMPN 1 Lembeyan for the 2023/2024 academic year. The sample was determined using the Cluster Random Sampling technique. The data analysis technique used in this research is the normality test and partial test or t-test with one sample T-Test statistics. Through the questionnaire, students' understanding of the rules and regulations was in the high category with the most respondents being in the percentage score of 56-41, with 49 respondents with a percentage of 82%. Meanwhile, the discipline of class VIII students is in the high category with the most respondents being in the percentage score of 84-63 with 53 respondents with a percentage of 88%. Based on the t test criteria, Ha is accepted and H0 is rejected. If the results of the data processing have been carried out, the results obtained are tcount = 0.001 and ttable = 0.05, this proves that tcount > ttable. This shows that there is a relationship between class VIII students' understanding of rules and discipline at SMPN 1 Lembeyan Magetan.